The Role of Efflux Pumps and Environmental pH in Bacterial Multidrug Resistance - NOVÉ, MÁRTA (In Vivo, 2020)
Background/Aim: One of the most studied bacterial resistance mechanisms is the resistance related to multidrug efflux pumps. In our study the pump activity of the Escherichia coli K-12 AG100 strain expressing the AcrAB-TolC pump system was investigated at pH 7 and pH 5 in the presence of the efflux pump inhibitor (EPI) promethazine (PMZ). Materials and Methods: The EPI activity was assessed by real-time fluorimetry. The influence of PMZ treatment on the relative expression of the pump genes acrA, acrB and their regulators marA, marB, marR, the stress genes soxS, rob, as well as the bacterial growth control genes ftsI, and sdiA were determined by RT-qPCR. Results: The EPI activity of PMZ was more effective at neutral pH. The PMZ treatment induced a significant stress response in the bacterium at acidic pH by the up-regulation of genes. Conclusion: The genetic system that regulates the activity of the main efflux pump is pH-dependent.